2005
DOI: 10.1080/10473289.2005.10464660
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Emission Factors for Open-Lot Dairies: Direct Measurements and Estimation by Nitrogen Intake

Abstract: Ammonia (NH 3 ) emissions contribute to the formation of secondary particulate matter (PM) 10 m and under (PM 10 ). Dairies are significant sources of NH 3 in the San Joaquin Valley (SJV) of California, where the National Ambient Air Quality Standard for PM 10 is frequently exceeded. Detailed descriptions of diets, animal demographics, and production levels were obtained for two commercial open-lot dairies in the SJV and used to compute nitrogen intake for each feeding group (g N day

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 15 publications
4
26
0
Order By: Relevance
“…Differences between the east basin and west basin emissions were in part due to the need to estimate upwind flux for the west basin versus the measurement of the upwind flux of the east basin. Ammonia emissions were comparable to those reported by Rumburg et al (2008) and generally higher than those reported by Cassel et al (2005a,b). Emissions as the basin dried and while the solid sludge was removed varied greatly.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Differences between the east basin and west basin emissions were in part due to the need to estimate upwind flux for the west basin versus the measurement of the upwind flux of the east basin. Ammonia emissions were comparable to those reported by Rumburg et al (2008) and generally higher than those reported by Cassel et al (2005a,b). Emissions as the basin dried and while the solid sludge was removed varied greatly.…”
Section: Resultssupporting
confidence: 77%
“…Rumburg et al (2008) measured NH 3 emissions of a dairy wastewater storage pond in Washington State over a range of temperatures and found emissions ranging from 31 to 150 μg −2 s −1 . Cassel et al (2005a,b) reported short‐term emissions ranging from 3 to 27 μg −2 s −1 downwind of manure basins of 2200‐ and 1500‐head open‐lot dairies in California. Bjorneberg et al (2009) measured NH 3 emissions from a 700‐milking‐cow, open‐lot dairy in Idaho during single days in January, March, June, and September and found emissions from the manure pond ranging from 6 μg −2 s −1 in January to 45 μg −2 s −1 in March.…”
mentioning
confidence: 99%
“…In both of these studies, measurements were taken for up to 5 d during one or two seasons. Other studies have determined NH 3 emissions from dairy cattle housing (Cassel et al, 2005; Rumburg et al, 2008) or dairy cattle housing and manure handling systems (Flesch et al, 2009) using downwind measurements and modeling to estimate emissions. These studies measured NH 3 emissions from 3 to 31 d, with some studies measuring emissions during different seasons (winter, summer, and fall).…”
mentioning
confidence: 99%
“…This was the most comprehensive study of emissions from livestock agriculture at the time; however, it did not include emissions of GHGs. Since then, additional peer‐reviewed studies have investigated emissions from livestock production in the United States, including beef (Todd et al, 2011, 2014), dairy (Cassel et al, 2005; Rumburg et al, 2008; Bjorneberg et al, 2009; Flesch et al, 2009; Leytem et al, 2011, 2013; Moore et al, 2014), swine (James et al, 2012; Rahman and Newman, 2012), and poultry (Miles et al, 2006; Moore et al, 2011; Hayes et al, 2013). Even with the completion of the NAEMS study, the USEPA Science Advisory Board (2013) recommended that more data are required before the USEPA develops emission methodologies for these livestock sectors, suggesting that quantification of on‐farm emissions is still a key area of future research.…”
Section: Key Research Areas and Needsmentioning
confidence: 99%